Experimental study on the backdraft phenomenon of solid fuel. - Jianlong Zhao (Public Library of Science (PLoS), 2021)
In this study, a series of small-scale experiments were conducted to investigate the backdraft phenomenon in a compartment (1.1 × 0.4 × 0.75 m) with woodblocks as fuel. This research focused on the effects of compartment window woodblock areas on backdraft time, with a video recording of the experimental phenomena. Thermocouples and a gas analyzer were used to measure the temperature and the concentration of gas components in the compartment, respectively. There was no additional heat source or ignition source pre-set in the compartment at the beginning of the experiments; the experimental processes only depended on the heat released from the burning or smoldering of woodblocks. When compartment ventilation improved, smoldering of woodblocks became intense, and backdraft occurred. The results show that backdraft time is shorten with increases of compartment window and woodblock areas, and opening the upper window of a compartment could avoid the backdraft phenomenon. The results help to understand the backdraft phenomenon of solid fuel and, more importantly, could help firefighters adopt reasonable fire-fighting strategies for restraining backdraft occurrence.